PENGARUH HUMAN CAPITAL TERHADAP KINERJA AUDITOR PADA KAP YANG ADA DI BANDUNG - Supriatna, Nono (Jurnal Riset Akuntansi dan Keuangan, 2014)
This research starting from the professionalism accountants as human capital at accountant firm as a service company. This research is intended  to study the effect of human capital on auditor performance at KAP in Bandung to propose the hypothesis that human capital has positive influence on auditors performance, either partially or simultaneously. Some dimensions of the sub-variables that make up the human capital that will be studied is represented by the factors individual capability, individual motivation, leadership, the organizational climate, and workgroup effectiveness. The auditor’s performance is measured by three factors that make up the performance:  (1) individual factor, (2) psychology factor, and (3) organization factor.            The research was conducted at the accounting firm located in Bandung. Of the number of samples taken at random population consisting of senior accountants and junior accountants as respondents. Technique of data collecting used  questionnaire. In accordance with the measurement scale, the data has been collected tested the validity of the formula Spearman Rank correlation and reliability with Cronbach alpha. The data has been tested and found valid and reliable then analyzed by correlation and regression analysis.            Based on the results of correlation and regression analysis to test hypotheses derived research findings that human capital simultaneously has a fairly close relationship with performance. While the multiple regression analysis known that each dimension contributes to the performance of the auditor's diverse and significant at p = 0.05, so the significance of test results, either partially or simultaneously can be concluded to accept the research hypothesis, namely human capital has positive influence on the performance of auditors.